PENGARUH KUALITAS PELAYANAN DAN WORD OF MOUTH TERHADAP NIAT BELI ULANG DI RUMAH MAKAN BU DESAK, KABUPATEN BADUNG - Putri, Ni Putu Arista Diana; Suasana, I Gst. A. Kt. Gd. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Repurchase intention is an activity that has taken the form of behavior or action in which consumers will commit to make purchases in the future. In addition, there is word of mouth promotion. The purpose of this study was to explain the effect of service quality, word of mouth on repurchase intentions. This research design uses a quantitative approach in the form of an associative approach. This research was conducted in Badung Regency, especially in Mengwi District. The object used in this study is the influence of service quality, word of mouth on repurchase intentions on the consumers of Bu Desak's Restaurant. The data analysis technique used is multiple linear regression. The results of this study show 1) Service quality has a positive and significant effect on repurchase intentions. 2) Word of mouth has a positive and significant effect on repurchase intention. 3) Quality of service, word of mouth on repurchase intention has a joint effect on repurchase intention. This research raises practical implications for Mrs. Desak's Restaurant so that they can use this research as an input for learning references.